Menu Close

Question 7: If then find out<br>
a. f(-1) b. f(0) c. f(1)

Solution

a. Since x = -1, we use the function f(x) = x – 3.
&therefore; f(-1) = -1-3 = -4

b. Since x = 0, we use the function f(x) = 2x + 5.
&therefore; f(0) = 2×0 + 5 = 5

c. Since x = 1 > 0, we use the function f(x) = 2x + 5.
&therefore; f(1) = 2×1 + 5 = 2 + 5 = 7

3 Comments

  1. Pingback:Exercise 1.1, Math’s 12

  2. Pingback:Exercise 1.1, Question 6

  3. Pingback:Math’s 12, Exercise 1.1, Question 8

Leave a Reply

Your email address will not be published. Required fields are marked *